The study of korean coach`s leadership style in Chinese Taipei archery team - Chien Ying, L.; De Long, L.; Li Kang, C.; Szu Yu, C.; Jo Yun, C. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Purpose: Chinese Taipei archery team has achieved international elite performance in recent years. Besides athletes` hard-work training and the intervention of sport science, the coach leadership played as an important factor. Chinese Taipei Archery Association hired Korean coach Koo Ja-Chung during 2013-2017. Chinese Taipei archery team started to reach out top-ranked performance among international tournaments stably, allocated 32 golds, 22 silvers and 33 blonde medals in the international competition within 4 years. Therefore, this study aimed to explore the coach Koo`s leadership style by interviewing athletes and coaches. Methods: This study used quantitative research method via semi-structured interview approach (Patton, 1990). The participants were Coach Koo, two assistant coaches, and athletes who coached by coach Koo in national team more than 6 months. The study used triangulation analysis to verify the interview data. Results: The results indicated Coach Koo showed a rather democracy leadership style, so that athletes receive greater autonomy-support behaviors. Meanwhile, Coach Koo gave out feedback for athletes accroding to thier individual needs. Therefore, the athletes formed higher self-recognition and the team created optimum competing climate. The athletes also agreed that Coach Koo established a sense of trust within the team by guiding leadership. Specifically, the support from coach Koo brought great confidence and peace of mind during competitions. Conclusion: the coach Koo`s leadership style was identified in this study as a decisive role led to the optimal archery performance worldwide for Chinese Taipei archery team. The leadership style of Coach Koo can be used as a reference for Taiwanese coaches.